Overview of obstetric patients and their outcome in a tertiary hospital of Bangladesh (BIRDEM Medical Journal, 2021)
Background: In developing countries like Bangladesh major population lives in rural areas, lacking access to essential obstetric facilities. Timely referral can reduce maternal morbidity and avoid maternal death in many instances. However lack of structured referral system is a major hurdle that delays proper management of such cases. The objective of the study was to review the pattern of obstetric cases admitted in our hospital, to study the clinical course and management of women during the hospital stay and to study the maternal and perinatal outcomes in terms of live birth or still birth, intra uterine fetal death and neonatal admission.Methods: It is a retrospective observational study conducted in the department of Obstetrics and Gynaecology, BIRDEM General Hospital, Dhaka, from July 2018 to June 2019, including2880 obstetric cases admitted in the hospital. Detailed history of the patients were taken, frequency of each disease was calculated separately. Management of the patient and mode of delivery were noted. Fetal outcome parameters like live or still birth and intra uterine fetal death were noted.Results: Among 3953 admitted patients, obstetric cases were 2880 (73%).Maximum number of patients were booked cases(84.09%) and 75% were from urban area. The patients were in the age group from 18 to 40 years,32% were primigravida and 68% were multi gravida. Majority of our admitted patients had either diabetes mellitus or gestational diabetes mellitus, 58.19% and 23.95% respectively. Common co morbidities and obstetric complications were hypertensive disorder of pregnancy, anaemia, premature rupture of membrane, oligohydramnios and fetal growth restriction. Among the 2084 delivered cases were delivered by ceasarean section (86.42%) 13.53% were delivered vaginally. Commonest indication for cesarean delivery was history of previous cesarean section.Conclusion: Wide spectrum of complicated obstetric cases were admitted to our tertiary care hospital. Many complicated patients were referred from different centers for special management. But delayed referral sometimes could not help properly and also resulted in a high number of cesarean section.BIRDEM Med J 2022; 12(1): 41-44